Catalysts for transport transitions: Bridging the gap between disruptions and change. (April 2017) - Kent, Jennifer; Dowling, Robyn; Maalsen, Sophia
Abstract: The ability of disruptions - big and small - to induce modal shift away from the private car is one of the more pressing concerns of transport geography and policy. Car sharing, a more sustainable mode of mobility to private car ownership, has quietly emerged as a viable and popular alternative to private vehicle travel in numerous cities of the world. This paper brings these two phenomena into conversation. We present a novel exploration of the precise moment in which the decision to start car sharing is made - an event which remains under-researched and little understood. Using a qualitative analysis of interview data to explore the period during which the individual adopts car sharing, we ask: how are transport transitions, particularly the uptake of car sharing, catalysed? We find that disruptions can either be single shocks, or a bundling and re-ordering of existing practices. We propose that willingness and ability as two preconditions that are key to enable transition to new ways of being mobile. Willingness is an embrace of new practices through inevitable teething problems. Ability is an aptitude for alternative practices, as well as access to infrastructure. Highlights: Transport transitions are often preceded by disruption. Disruptions can be either single shocks or a bundling and re-ordering of practices. Ability and willingness to change are common preconditions to mobility transitions. Ability is an aptitude for alternative practices as well as access to infrastructure. Willingness is an embrace of new practices through inevitable teething problems.